Ethics and positionality in qualitative research with vulnerable and marginal groups. (June 2020) - Shaw, Rhonda M.; Howe, Julie; Beazer, Jonathan; Carr, Toni
Social scientists are increasingly attentive to the practical importance of research ethics and professional codes of conduct when undertaking studies with human participants, especially around sensitive topics. In New Zealand, the social and cultural context of research praxis is also shaped by institutional principles that ensure research participants feel safe, respected, and heard when participating in research, and that the knowledge outcomes of the research process will be disseminated and shared with relevant cultural groups. In this article, we present four case studies based on projects that discuss researcher positionality in relation to the ethical and emotional work involved in undertaking research on sensitive topics with individuals from vulnerable and marginal groups. In doing so, we foreground the importance of articulating and managing emotion in research on sensitive topics, and suggest measures to ensure the well-being of researchers engaged in studies of this kind.